Credit Rating Agencies - Katz, Jonathan (World Bank, Washington, DC, 2012)
In the United States and Europe faulty credit ratings and flawed rating processes are widely perceived as being among the key contributors to the global financial crisis. That has brought them under intense scrutiny and led to proposals for radical reforms. The ongoing debate, while centered in major developed markets, will also influence policy choices in emerging economies: whether to focus on strengthening the reliability of ratings or on creating alternative mechanisms and institutions that can perform more effectively the role that in developed markets has traditionally been conferred on credit rating agencies.